Differentiation of sea buckthorn syrups processed by high pressure, pulsed electric fields, ohmic heating, and thermal pasteurization based on quality evaluation and chemical fingerprinting - Sevenich, Robert; Gratz, Maximilian; Hradecka, Beverly; Fauster, Thomas; Teufl, Thomas; Schottroff, Felix; Chytilova, Lucie Souckova; Hurkova, Kamila; Tomaniova, Monika; Hajslova, Jana; Rauh, Cornelia; Jaeger, Henry (Frontiers in Nutrition, 2023)
Impact of processing on product characteristics, sustainability, traceability, authenticity, and public health along the food chain becomes more and more important not only to the producer but also to the customer and the trust of a consumer towards a brand. In recent years, the number of juices and smoothies containing so called super foods or fruits, which have been “gently pasteurized”, has increased significantly. However, the term “gentle pasteurization” related to the application of emerging preservation technologies such as pulsed electric fields (PEF), high pressure processing (HPP) or ohmic heating (OH) is not clearly defined. Therefore, the presented study investigated the influence of PEF, HPP, OH and thermal treatment on quality characteristics and microbial safety of sea buckthorn syrup. Syrups from two different varieties were investigated under the following conditions HPP (600 MPa 4-8 min), OH (83 °C and 90 °C), PEF (29.5 kV/cm, 6 µs, 100 Hz) and thermal (88 °C, hot filling). Analyses to test the influence on quality parameters like ascorbic acid (AA), flavonoids, carotenoids, tocopherols, antioxidant activity; metabolomical/chemical profiling (fingerprinting) via U-HPLC-HRMS/MS (here especially flavonoids and fatty acids); sensory evaluation, as well as microbial stability including storage, were conducted. Independent from the treatment, the samples were stable over 8 weeks of storage at 4 °C. The influence on the nutrient content (Ascorbic acid (AA), total antioxidant activity (TAA), total phenolic compounds (TPC), tocopherols (Vit E)) was similar for all tested technologies. Employing statistical evaluation Principal Component Analysis (PCA) a clear clustering based on the processing technologies was observed. Flavonoids as well as fatty acids were significantly impacted by the type of used preservation technology. This was obvious during the storage time of PEF and HPP syrups, where enzyme activity was still active. The color as well as taste of the syrups were found to be more fresh-like for the HPP treated samples.